A bacterial cytokine - Mukamolova, Galina V. (The National Academy of Sciences, 1998)
Viable cells of Micrococcus luteus secrete a factor, which promotes the resuscitation and growth of dormant, nongrowing cells of the same organism. The resuscitation-promoting factor (Rpf) is a protein, which has been purified to homogeneity. In picomolar concentrations, it increases the viable cell count of dormant M. luteus cultures at least 100-fold and can also stimulate the growth of viable cells. Rpf also stimulates the growth of several other high G+C Gram-positive organisms, including Mycobacterium avium, Mycobacterium bovis (BCG), Mycobacterium kansasii, Mycobacterium smegmatis, and Mycobacterium tuberculosis. Similar genes are widely distributed among high G+C Gram-positive bacteria; genome sequencing has uncovered examples in Mycobacterium leprae and Mb. tuberculosis and others have been detected by hybridization in Mb. smegmatis, Corynebacterium glutamicum, and Streptomyces spp. The mycobacterial gene products may provide different targets for the detection and control of these important pathogens. This report is thus a description of a proteinaceous autocrine or paracrine bacterial growth factor or cytokine.